Information and Communication Technology (ICT) Integration in Teaching English for Young Learners - Wati, Siska Oktawidya; Zaim, M.; Thahar, Harris Effendi (Aulad: Journal on Early Childhood, 2025)
Information and communication technology is not a new issue in education world, but it is interesting to follow its development. Teachers can use this kind of technology to increase work ethos. Besides, this technology makes it possible to do many kinds of activity fast, precisely, and accurately. The development of information technology shows that there appears varieties of activity based on technology. Teaching English as second language becomes more challenging to teach, particularly for young learners. The  research  method  used  Systematic  Literature  Review,  namely  a  literature  search  both  international  and  national  using  the  Google Scholar  website.  Data  collection  was  carried  out  by  documenting  and  reviewing  all  articles  related  to  ICT media in English for young learners. So  it  can  be  concluded  that  the  use  of  ICT  media  in  early  childhood  English  learning  can  be  done  and  has  a  positive  impact  that  benefits  both  teachers and children.